BUILDING RESILIENT FOUNDATIONS: A FOCUS ON SOCIAL WORK EDUCATION IN STRENGTHENING DISASTER PREPAREDNESS IN BOTSWANA - Kgosi, Molefi Tumelo (Journal of Current Research and Review (JCRR), 2023)
Social work, as a dynamic profession, addresses a wide range of issues affecting human society. These issues encompass diverse problems that differ in type, scale, and intensity. Among these challenges are natural disasters, which have global implications, leading to infrastructure destruction, loss of lives, economic setbacks, and environmental harm. Botswana, like many other nations, faces its share of natural disasters, primarily including drought, floods, wildfires, animal diseases, earthquakes, pest infestations, epidemics, and the ongoing challenges posed by HIV and AIDS. Drought is a pervasive issue affecting the entire country, while floods typically occur during the rainy season from October to March. Veld fires are a common occurrence during the dry months from April to November, with a peak in July. In 1999/2000, Botswana witnessed one of the most devastating flood events, which affected 23 administrative districts, cities, towns, and villages. This catastrophe resulted in significant loss of life, extensive damage to over 17,000 structures (comprising both public and private assets), environmental degradation, crop destruction, and the displacement of thousands of people. This paper explores the role of social workers in addressing the multifaceted challenges posed by natural disasters in Botswana. It delves into the unique aspects of various disasters, their impacts on communities, and the critical interventions social workers undertake to provide support, relief, and rehabilitation. By examining these disaster scenarios, this study sheds light on the vital role of social work in enhancing disaster resilience, safeguarding lives, and promoting community well-being in the face of these diverse natural challenges.